Strategi Preventif Penggunaan NAPZA Berbasis Pemberdayaan (Studi Kasus Pondok Pesantren Al-Isti'anah Kabupaten Pati) - Kharis, Ahmad (Al-I'timad: Jurnal Dakwah dan Pengembangan Masyarakat Islam, 2023)
The use of Narcotics, Alcohol, Psychotropic Substances, and Other Addictive Substances (NAPZA) has become a serious problem in various segments of society, including among students in Islamic boarding schools. This research aims to develop and analyze empowerment-based prevention strategies for NAPZA use at the Al-Isti'anah Boarding School in Pati Regency. The study adopts a qualitative approach with a case study research design. Data were collected through in-depth interviews with the leaders of the boarding school, teachers, and students. Additionally, participatory observation and document analysis were conducted to obtain a comprehensive overview of the context and dynamics within the boarding school. The results of the research indicate that Al-Isti'anah Boarding School has implemented various empowerment-based prevention strategies for NAPZA use. These strategies include the establishment of educational programs on the dangers of NAPZA, the development of social skills, the cultivation of religious and moral values, and the creation of an environment that supports and reinforces healthy lifestyle choices. Empowerment is achieved by actively involving all stakeholders, including leaders, teachers, students, and families. Various activities such as archery, wood carving, local food cultivation, and graphic design of calligraphy are conducted to divert specific concentrations on the negative impacts of NAPZA use.